Efektivitas Program Balai Latihan Kerja (BLK) Dalam Upaya Penurunan Tingkat Pengangguran Berdasarkan Perspektif Ekonomi Islam Di Kota Payakumbuh - Annisa Mardhotillah Maulina; Gina Havieza Elmizan (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effectiveness of the Vocational Training Center (BLK) program in reducing unemployment in Payakumbuh City. The study employed qualitative methods with field research. Data collection techniques included interviews, observation, and documentation. The results indicate that the BLK program is effective based on nine indicators. The program is able to help the community improve their skills and work abilities. The implementation strategy involved socialization and a survey of participant needs. The available facilities and infrastructure were deemed adequate, and all training costs were covered by the government. The program was structured and directly monitored by competent instructors. The training duration was deemed effective in improving participant skills. Furthermore, the program's targeting was deemed appropriate, as it targeted communities in need of job training, thus supporting efforts to reduce unemployment in Payakumbuh City.